Calculating Expected Stock Return Using Arbitrage Pricing Theory Model and Analyzing Independent Variables That Affect Stock Expected Return (Analysis Conducted on Kompas100 Stock Issuers For The Period 2020 – 2022) - Harold Kevin Alfredo (Publikasi Indonesia, 2023)
This study aims to determine which variabel independent (IHSG, USD exchange, money supply (M2), and inflation) that has the most influence of expected returns using Arbitrage Pricing Theory Model for selected stock issuers from the KOMPAS100 Index for the period 2020 – 2022. The population in this study are all stock issuers registered as members of the KOMPAS100 Index for the period 2020 – 2022 using a purposive sampling technique to obtain 57 selected stock issuers from the KOMPAS100 Index population for the period 2020 – 2022. Data on stock issuers who are members of the KOMPAS100 Index for the period 2020 – 2022 is taken from the doktorsaham.com website. The monthly stock price data for selected issuers and the monthly JCI stock data are taken from the Investing.com website. Monthly inflation data for the period 2020 - 2022 is taken from the BI.go.id website. Monthly data on the amount of money in circulation (M2), and monthly data on the USD exchange rate for the period 2020 – 2022 are taken from the satudata.kemendag.go.id website. Arbitrage Pricing Theory is used to calculate the expected return of a sample of selected stock issuers using the Microsoft Excel application. JASP application is used to test the hypothesis using Linear Regression.